Kūkai 空海 (774–835) and Saichō's 最澄 (766–822) theories on gotra 種姓 (caste). Issue 2 (3rd July 2021) - Li, Zijie
ABSTRACT: In this article, I argue that although the Pusa yingluo benye jing 瓔珞本業經 [Sutra of the Diadem of the Primary Activities of the Bodhisattvas] utilised the theory of zhongxing 種姓 (Skt. gotra ; Jp. shushō ; caste) in the Pusa dichi jing 菩薩地持經 [Sutra of Stages of Bodhisattvas], the Pusa yingluo benye jing changed the explanation of zhongxing with the stages of bodhisattvas. According to Kūkai and Saichō's interpretations of shushō related issues, the Pusa dichi jing and the Pusa yingluo benye jing were still mainstream. The theory of zhongxing in these two texts strongly influenced their thoughts on shushō .